The Effect of Repetitive Transcranial Magnetic Stimulation (rTMS) on Cognition in Patients With Traumatic Brain Injury: A Protocol for a Randomized Controlled Trial - Zhang, Han; Zhao, Yu; Qu, Yun; Huang, Yunyun; Chen, Zhu; Lan, Hong; Peng, Yi; Ren, Hongying (Frontiers in Neurology, 2022)
Cognitive impairment, defined as a decline in memory and executive function, is one of the most severe complications of traumatic brain injury (TBI). Patients with TBI are often unable to return to work due to cognitive impairment and their overall quality of life is reduced. TBI can bring a serious economic burden to patient's families and to society. Reported findings on the efficacy of repetitive transcranial magnetic stimulation (rTMS) in improving cognitive impairment following TBI are inconsistent. The purpose of the proposed study is to investigate whether rTMS can improve memory and executive function in patients with TBI. Herein, we propose a prospective randomized placebo-controlled (rTMS, sham rTMS, cognitive training), parallel-group, single-center trial. 36 participants with a TBI occurring at least 6 months prior will be recruited from an inpatient rehabilitation center. Participants will be randomly assigned to the real rTMS, sham rTMS, or cognitive training groups with a ratio of 1:1:1. A 20-session transcranial magnetic stimulation protocol will be applied to the left and right dorsolateral prefrontal cortices (DLPFC) at frequencies of 10 Hz and 1 Hz, respectively. Neuropsychological assessments will be performed at four time points: baseline, after the 10th rTMS session, after the 20th rTMS session, and 30 days post-intervention. The primary outcome is change in executive function assessed using the Shape Trail Test (STT). The secondary outcome measures are measures from neuropsychological tests: the Hopkins Verbal Learning Test (HVLT), the Brief Visuospatial Memory Test (BVMT), the Digit Span Test (DST). We report on positive preliminary results in terms of improving memory and executive function as well as beneficial changes in brain connectivity among TBI patients undergoing rTMS and hypothesize that we will obtain similar results in the proposed study.